Climate-proofing rice farming in Vietnam - International Center for Tropical Agriculture (2014)
It’s flood season in the lower Mekong Delta. Yet while the 17 million farmers living on the Delta in Vietnam’s southern-most tip - where 60 percent of the country’s rice is produced - are no stranger to flooding, climate change is throwing a curve ball.